Systematics of Neotropical electric knifefish Tembeassu (Gymnotiformes, Apteronotidae). Issue 1 (31st December 2022) - Peixoto, Luiz A. W.; Campos-da-Paz, Ricardo; Menezes, Naércio A.; Santana, C. David De; Triques, Mauro; Datovo, Aléssio
Abstract : A new species of the poorly known and critically endangered ghost knifefish Tembeassu is described from the upper Paraná and Araguari rivers, Brazil, using external anatomy and X-ray microcomputed tomography (µCT scan). Tembeassu titanicus sp. nov. is distinguished from its sole congener, T. marauna, by a unique set of morphometric and meristic characters, in addition to the absence of a tooth patch at the anterior portion of the roof of the oral cavity and the external corner of the mouth slightly passing the vertical through the posterior margin of the posterior nare. To test the monophyly of Tembeassu and reassess its phylogenetic position, a total-evidence approach was performed through a Bayesian inference (BI) and maximum-parsimony analysis (MP). Our results indicate that Tembeassu is monophyletic and the sister taxon of a clade formed by Apteronotus s.s., Megadontognathus, and Parapteronotus (BI); or as part of a large polytomy at the base of Apteronotidae (MP). Species of Tembeassu co-occur in the Paraná River basin, and the absence of the patch of accessory teeth in T. titanicus sp. nov. may indicate that this species accesses a different food resource, and also putatively occupies a different habitat than T. marauna . Comments on the evolution of the mandibular lobe in Gymnotiformes, dentition pattern in Tembeassu, and apteronotid diversity in the Paraná River are provided. http://zoobank.org/urn:lsid:zoobank.org:act:691CB9A5-5CDB-4BF9-8A6FEAE877563C12